Influences of solvent types on the formation of graphene in the electrochemical exfoliation method - Kurniawan, Tedi; Anwar, M. A.; Oktiani, R.; Ragadhita, R.; Nandiyanto, A. B. D.; Aziz, M. (Institute of Problems of Mechanical Engineering RAS, 2019)
The aim of this study was to evaluate the effect of different solvents in sonication process on the formation of graphene from the electrochemical exfoliation of graphite. In short, graphite rod was exfoliated by electrochemical process with ammonium sulfate as saltelectrolyte. The exfoliated powder then sonicated under two different solvents, which are Dimethylformamide (DMF) and aqueous solution to form graphene. It was found that similar structure of graphene was obtained from both types of solvent. However, the amount of graphene produced was different due to the differences in graphene stability. Graphene is more stable in DMF solvents compared to the aqueous solution. The aqueous solution can allow the reversible reaction that can reform graphite oxide from graphene due to the existence of hydroxyl component in the aqueous solution